Creative Economy in the Sharia Framework: The Role of SMEs in West Sumatra - Afifah, Nur; Purnamasari, Pupung; Puji Lestari, Etty (Al Urwah : Sharia Economics Journal, 2025)
This study explores the role of small and medium-sized enterprises (SMEs) in West Sumatra in contributing to Indonesia’s economic revival through a Sharia-compliant creative economy. Using a quantitative research design and a sample of 150 respondents, including both business owners and consumers, the research investigates the relationships between the creative economy, Sharia framework, product innovation, and public acceptance of the Sharia economy, with economic revival as the dependent variable. Data were analyzed using Smart PLS, revealing that public acceptance of the Sharia economy mediates the relationship between the creative economy and economic revival, as well as between the Sharia framework and economic revival. The findings show that while the creative economy's direct impact on economic recovery is limited, public trust in Sharia-compliant business practices significantly enhances this relationship. Similarly, the Sharia framework plays a key role in driving economic revival, with public acceptance amplifying its effects. These results underscore the importance of aligning innovation and ethical compliance with public values to foster sustainable economic growth in Sharia-based economies. The study provides valuable insights for policymakers and business leaders on the critical role of public acceptance in leveraging the potential of SMEs for economic recovery.